Discovery of plasma biomarkers related to blood-brain barrier dysregulation in Alzheimer's disease - Dan Yuet Ruh (Nanyang Technological University, 2024)
Alzheimer’s disease (AD) is the most common cause of dementia. However, current diagnostic tools are subjective, cost-inefficient, and difficult to administer. Blood-based biomarkers, which are quantitative and non-invasive, have thus been increasingly investigated as potential diagnostic tools. Exploiting the well-established blood-brain barrier (BBB) dysregulation in AD, this study hypothesized that with BBB dysfunction, brain-synthesised proteins could leak into peripheral circulation for increased detection. Differential abundance analysis was performed on pooled datasets of plasma and brain proteomics, and integration revealed a novel panel of 5 plasma proteins which yielded an AUROC of 0.70 in a separate plasma dataset: APOD, B2M, CFH, CLU and C3. Proteins were confirmed to be associated with AD neuropathology and disassociated with peripheral inflammation and other neurodegenerative diseases. Single-cell transcriptomics revealed an upregulation of 4 of the protein transcripts in AD astrocytes, mediated by 3 transcription factors involved in neuroinflammation that are upregulated in AD: JUNB, CEBPB and ZEB1. CLU was further shown to regulate the downstream expression of neuronal death genes. Interestingly, preliminary evidence implicated the LRP receptor family in brain-to-blood protein leakage in AD. Future research should investigate the regulation of this receptor-mediated transcytosis pathway in AD and validate the biomarker panel in clinical samples.